Preferensi Teknologi, Perencanaan dan Pengambilan Keputusan Keuangan Berdasar Literasi Keuangan Syariah - Arizal Hamizar; Fatmah Watty Pelupessy; Dety Aryani Relubun; Muhammad Reza Nacikit; Afdhal Yaman; Muammar W. Maruapey; Fadli Fendi Malawat; Soenari Soenari (CV. ULIL ALBAB CORP, 2025)
This research aims to analyze the influence of Islamic financial literacy on students' financial decision-making behavior, particularly in the context of financial technology (fintech) adoption. The study focuses on understanding how students’ preferences, trust, and comprehension of Islamic financial literacy affect their decisions in using fintech services and its impacts. This research employs a qualitative approach with an exploratory method, involving in-depth interviews with students from various majors and universities in Ambon City. Data were analyzed using a thematic method, identifying and interpreting key themes such as preferences toward fintech, trust levels, and the influence of fintech on students' financial decisions in depth. The results show that students have a high preference for fintech due to factors like efficiency, convenience, and accessibility. However, trust levels in fintech are influenced by perceptions of risk and data security. Islamic financial literacy plays a significant role in shaping students’ preferences for Sharia-based fintech services. Furthermore, fintech adoption has been proven to influence students’ financial planning, particularly in encouraging more practical and efficient financial management behavior, while also presenting challenges in maintaining consistency with Sharia financial principles.